Answer:
Explanation:
(44=6x-1+9x.-5)
We move all terms to the left:
(44-(6x-1+9x.-5))=0
We add all the numbers together, and all the variables
(44-(6x+9x.-6))=0
We calculate terms in parentheses: +(44-(6x+9x.-6)), so:
44-(6x+9x.-6)
determiningTheFunctionDomain
-(6x+9x.-6)+44
We get rid of parentheses
-6x-9x.+6+44
We add all the numbers together, and all the variables
-6x-9x.+50
Back to the equation:
+(-6x-9x.+50)
We get rid of parentheses
-6x-9x.+50=0
We move all terms containing x to the left, all other terms to the right
-6x-9x.=-50